Ethical and conceptual challenges in researching human trafficking in Edo state, Nigeria - Diagboya, Precious (Trends in organized crime, 2023)
The aim of this paper is to further understanding on the ethical and conceptual challenges associated with researching human trafficking in Edo state, Nigeria. The contribution addresses perceptions of these phenomena among some local actors in the state. Based on five years’ research on human trafficking from Nigeria to Europe, this paper puts into perspective local perceptions, and some dynamics of data collection. Also considered here are ethical challenges bordering on trust and suspicion of the researcher’s intent, informed consent and suspicion of researcher’s motive especially those linked to funding. The paper concludes by recommending ways of navigating as well as overcoming the associated challenges in researching human trafficking in Edo state.